2018
DOI: 10.1111/jmft.12323
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Adults: A National Survey on Depression, Religious Fundamentalism, Parent Relationship Quality & Acceptance

Abstract: Sexual minority persons from religious families may experience low acceptance by parents, however, little is known about the relationship of religiosity and parent relationships on mental health into adulthood. This study sought to test a moderated mediation model predicting depression based on religious fundamentalism, parent acceptance, and parent-child relationship quality. Sexual minority adult participants (n = 384) from across the U.S. completed a web-based, anonymous survey. Results found a conditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Through a qualitative investigation, Dahl and Galliher (2012) found that CO in religious environments could lead to both positive and negative outcomes, with the latter including feelings of inadequacy, religious-related guilt, depressive symptoms, and social strain. Additionally, high family religiosity has been found to be strongly associated with parents' rejection of LGBQ+ children (Baiocco et al, 2015;Snapp et al, 2015;Heiden-Rootes et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Through a qualitative investigation, Dahl and Galliher (2012) found that CO in religious environments could lead to both positive and negative outcomes, with the latter including feelings of inadequacy, religious-related guilt, depressive symptoms, and social strain. Additionally, high family religiosity has been found to be strongly associated with parents' rejection of LGBQ+ children (Baiocco et al, 2015;Snapp et al, 2015;Heiden-Rootes et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…While semistructured interviews offered detailed descriptions of the psychotherapy experiences and connections to family, religious upbringings, and personal religious beliefs. This article is reporting on one part of a larger study on the experiences of LGBQ adults from religious families (see Heiden‐Rootes et al, 2018; Heiden‐Rootes et al, 2019). The study was approved by the authors’ university's IRB.…”
Section: Methodsmentioning
confidence: 99%
“… Family religious fundamentalism is an established measure with a range of 0–100. See Heiden‐Rootes et al 2019 for full description of the measure. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations